Evaluation of cover crops in reducing Spongospora subterranea inoculum through qPCR and microscopy assays - Alaryan, Maryam M., author; Charkowski, Amy, advisor; Stewart, Jane, committee member; Wrighton, Kelly, committee member (Colorado State University. Libraries, 2021)
Cover crops have been used for years as an effective practice to manage soil-borne pathogens. Beside their other beneficial properties in enhancing soil quality and fertility, they can suppress soil-borne pathogens and reduce their populations in the soil. Spongospora subterranea is a soil-borne obligate biotrophic plasmodiophorid that causes powdery scab on potato tubers and gall formation on roots. Powdery scab tuber lesions are filled with resting spores (sporosori) and reduce potato quality and marketability. S. subterranea also vectors Potato mop-top virus, which causes necrotic arcs and spraing in tuber flesh. Currently, there are no effective methods to manage S. subterranea, which has a wide host range in addition to potato. This study was conducted to determine whether cover crops can decrease S. subterranea population levels in the soil. Eighteen cover crops, including legumes and mustards were assessed, and for each plant line, five plants were grown in individual pot that was inoculated with 10 sporosori/g of potting mix by comparison with five plants that were grown in non-inoculated potting mix. After harvest, plant roots were stained using trypan blue and examined under the light microscope, and qPCR was performed to determine S. subterranea inoculum level in the potting mix. The results suggested that S. subterranea invaded all the cover crop roots; however, the pathogen was unable to complete its life cycle on eleven out of eighteen cover crops based on post-harvest qPCR results. To confirm our results, a follow up experiment was conducted by inoculating the potting mix with 40 sporosori/g to better detect the pathogen, in addition to autoclaving the peat moss prior to planting. The roots were stained with DAPI after harvest and examined under the fluorescence microscope and S. subterranea DNA levels was quantified in the eleven cover crops by qPCR. The results showed that buckwheat, barley, and legumes have the potential to stop the pathogen from increasing in the soil where there was no significant increase in the inoculated samples in most of the tested cover crops. The results from this experiment will be used to guide in-field cover crop experiments and to advise farmers on cover crops that may not increase the inoculum levels of S. subterranea in the soil.
Keywords: potato; soil-borne pathogen; cover crops; Spongospora subterranea; powdery scab